2011 IEEE 13th Electronics Packaging Technology Conference 2011
DOI: 10.1109/eptc.2011.6184432
|View full text |Cite
|
Sign up to set email alerts
|

Green mould compounds: Impact on second level interconnect reliability

Abstract: The change-over from conventional to so-called green moulding compounds has gradually taken place in the last five years. These green mould compound materials have a lower thermal expansion and higher elastic modulus. As a consequence of the modified thermal and mechanical properties, an impact on the thermo-mechanical behaviour of the package-board assembly is expected (so-called Package Board Interaction: PBI). The CTE difference between the package and the board increases introducing the green mould compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…A side effect of the lower CTE is that the E-modulus increases (due to higher content of silica particles). In reference [1], it was shown that the product of E-modulus and CTE is about a constant value. Fig.…”
Section: High Cte Versus Low Cte Overmold Compound: Impact On Wire Bomentioning
confidence: 99%
See 2 more Smart Citations
“…A side effect of the lower CTE is that the E-modulus increases (due to higher content of silica particles). In reference [1], it was shown that the product of E-modulus and CTE is about a constant value. Fig.…”
Section: High Cte Versus Low Cte Overmold Compound: Impact On Wire Bomentioning
confidence: 99%
“…As a low CTE overmold materials have some benefit regarding CPI, it is of interest to know from which CTE on . In reference [1], it was shown that the elastic modulus varies inversely proportional to the CTE of overmold. Therefore, six different overmolds are selected ( Table 4).…”
Section: Parameter Studymentioning
confidence: 99%
See 1 more Smart Citation
“…As electronics can be subjected to temperature cycling, the larger expansion/shrinkage mismatch between the board and component will increase the loading on the solder joint providing the electrical but also mechanical connection between package and board. The concern of the low-CTE mold compound packages has been first reported in 2011 [1]. Only few other references show some results on different mold compounds [2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for BGAs produced using these new low-CTE moulding compounds, also the part of the BGA outside the chip area will have a rather low CTE. Simulations done by imec have shown that this may decrease the fatigue life of the solder joints with up to 85% [5,6].…”
Section: Introductionmentioning
confidence: 99%